Structural, electrical and dielectric characterization of TeO2–WO3–Y2O3–Er2O3–Yb2O3 glasses. (August 2015) - Prezas, P.R.; Soares, M.J.; Freire, F.N.A.; Graça, M.P.F.
Graphical abstract: Highlights: TeO2 –WO3 –Y2 O3 –Er2 O3 –Yb2 O3 glasses were prepared by the melt quenching technique. σ dc is assigned to small-radius polaron (SRP) hopping between W 5+ and W 6+ states. σ ac is assigned to a dipolar mechanism between the modifiers and non-bridging oxygen. TeO2 –WO3 –Y2 O3 –Er2 O3 –Yb2 O3 glasses are promising for optoelectronic applications. Abstract: TeO2 based glasses with molar composition (70- x - y )TeO2 –20WO3 –10Y2 O3 – x Er2 O3 – y Yb2 O3, where x = 0 and 0.5 mol% and y = 0, 0.5, 1, 2 and 4 mol%, were prepared by the melt quenching technique. At room temperature all the samples are transparent, mechanical and thermally stable. The XRD results showed the amorphous nature of all the samples and the Raman spectra showed a band distribution related with TeO and WO bond vibrations. The introduction of WO3 results in a bandwidth substantially larger when compared to SiO2 based glasses and even other TeO2 based glasses, making this vitreous system promising for Raman optical amplification. In this work, the measurement and analysis of the electrical properties of this glass system was made. It was found that the hopping of small radius polarons, for small concentrations of networks modifiers, is the dominant process in the charge transport mechanism for the dc conductivity. For higher concentrations of ions structurally inserted in the glass network, the ionic conductivity starts to have an important role in the transport mechanism. The ac conduction mechanism was attributed to a dipolar process between the interstitial modifier cations and the nonbridging oxygen ions. For all samples, the dielectric constant is practically independent of the temperature and the frequency. This quantity tends to decrease with the increase of the concentration of Yb 3+ cations. No dielectric relaxation phenomenon was observed in the temperature and frequency measurement range.